2017
DOI: 10.1073/pnas.1710966114
|View full text |Cite
|
Sign up to set email alerts
|

Psychological targeting as an effective approach to digital mass persuasion

Abstract: SignificanceBuilding on recent advancements in the assessment of psychological traits from digital footprints, this paper demonstrates the effectiveness of psychological mass persuasion—that is, the adaptation of persuasive appeals to the psychological characteristics of large groups of individuals with the goal of influencing their behavior. On the one hand, this form of psychological mass persuasion could be used to help people make better decisions and lead healthier and happier lives. On the other hand, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
449
2
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(482 citation statements)
references
References 31 publications
8
449
2
23
Order By: Relevance
“…Additionally, the present study contributes to research seeking to better understand the extent to which knowledge of voters' core psychological characteristics and biases could be exploited in order to influence the way in which those voters form early opinions and subsequently process and interpret information. The importance of such research has been underlined in nascent studies which have demonstrated the effectiveness of categorizing, targeting, and influencing online social network users based on their personalities (Matz et al, 2017(Matz et al, , 2015Sumner, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the present study contributes to research seeking to better understand the extent to which knowledge of voters' core psychological characteristics and biases could be exploited in order to influence the way in which those voters form early opinions and subsequently process and interpret information. The importance of such research has been underlined in nascent studies which have demonstrated the effectiveness of categorizing, targeting, and influencing online social network users based on their personalities (Matz et al, 2017(Matz et al, , 2015Sumner, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…While the use of messages designed to resonate with certain personality traits and not others are not new, nascent research suggests that data from online social networks could enable anyone to create and amplify messages which play on inherent beliefs and primary emotions. These messages can then be directed to increasingly narrowly defined audiences (Matz, Kosinski, Nave, & Stillwell, 2017;Matz, Popov, Stillwell, & Kosinski, 2015;Sumner, 2017). While much of the recent media attention has focused on advertising, online social networks could be leveraged in other ways, such as testing and refining messages for use in wider campaigns, both on and offline.…”
Section: Personality and Cognition In The Eu Referendum 40mentioning
confidence: 99%
“…A natural next step in the HRWP approach is to identify the person characteristics that reliably predict individual differences in the effect of a situation feature or manipulation. This aim is practically important for work on psychological targeting to influence behavior (Matz, Kosinski, Nave, & Stillwell, ). Moreover, at a theoretical level, identifying the person characteristics serves to understand the nature of person‐situation interactionism (Shoda, ; Wood & Brumbaugh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another not further discussed challenge concerns data protection issues, because, with the ubiquitous IoT, everything we do will leave a trace. The emerging discipline of Psychoinformatics demonstrated already in first studies what insights can be derived from digital traces of the IoT with respect to psychodiagnostics on individual level (see for a review [40,128,129]; see also a recent interesting work on the potential of psychological targeting [130] perhaps in parts also endangering democratic processes [131]). To present the reader with a short summary of the most important research avenues to be tackled in the near future, according to this review/hypothesis paper, we add the following short bullet points:…”
Section: Conclusion and Limitationsmentioning
confidence: 99%